2015
DOI: 10.1128/jvi.01194-15
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin with High-Titer In Vitro Cross-Neutralizing Hepatitis C Virus Antibodies Passively Protects Chimpanzees from Homologous, but Not Heterologous, Challenge

Abstract: cThe importance of neutralizing antibodies (NAbs) in protection against hepatitis C virus (HCV) remains controversial. We infused a chimpanzee with H06 immunoglobulin from a genotype 1a HCV-infected patient and challenged with genotype strains efficiently neutralized by H06 in vitro. Genotype 1a NAbs afforded no protection against genotype 4a or 5a. Protection against homologous 1a lasted 18 weeks, but infection emerged when NAb titers waned. However, 6a infection was prevented. The differential in vivo neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 54 publications
(73 reference statements)
1
47
0
Order By: Relevance
“…We used purified polyclonal IgG antibodies (H06 IgG) isolated from genotype 1a chronic-phase patient H plasma collected in 2006,22 31 as well as monoclonal antibodies AR3A, AR4A and AR5A with the b6 control antibody 3233 We plated 6×10 3 Huh7.5 cells/well into poly- d -lysine-coated 96-well plates (96 Well Optical Bottom Plates, Nunc).…”
Section: Methodsmentioning
confidence: 99%
“…We used purified polyclonal IgG antibodies (H06 IgG) isolated from genotype 1a chronic-phase patient H plasma collected in 2006,22 31 as well as monoclonal antibodies AR3A, AR4A and AR5A with the b6 control antibody 3233 We plated 6×10 3 Huh7.5 cells/well into poly- d -lysine-coated 96-well plates (96 Well Optical Bottom Plates, Nunc).…”
Section: Methodsmentioning
confidence: 99%
“…This failure to consistently prevent infection with heterologous challenge viruses was confirmed in the chimpanzee study [268]. Thus, although a chronic-phase antibody sample has similar in vitro neutralization titers against homologous and heterologous strains [130,195] there is incomplete in vivo protection against the heterologous strains.…”
Section: Protective Immunity Of Neutralizing Antibodies Against Hcvmentioning
confidence: 75%
“…Subsequently, it was shown that immunoglobulin infused pre-challenge and during weeks 3 and 4 post-challenge could suppress the homologous infection for at least 4 months in the chimpanzee model [268]. Thus, for the homologous strain polyclonal immunoglobulin with in vitro neutralizing activity could control viremia in vivo.…”
Section: Protective Immunity Of Neutralizing Antibodies Against Hcvmentioning
confidence: 98%
“…However, sterilizing immunity mediated by antibodies is a challenging endpoint for preventive HCV vaccines. One recent study demonstrated that passive immunization of chimpanzees with antibodies that broadly neutralized infectivity of several HCV genotypes in cell culture only delayed infection with homologous virus and failed to protect against heterologous virus strains[24]**. Antibodies may nonetheless contribute to suppression of acute phase virus replication and perhaps resolution of infection.…”
Section: Vaccines To Prevent Primary Hcv Infectionmentioning
confidence: 99%
“…Animals studies have also been instructive. Transfer of neutralizing antibodies to chimpanzees after challenge with HCV resulted in at least transient suppression of viremia[22,24,29]. Neutralizing antibodies expressed from the genome of a recombinant AAV vector also facilitated clearance of HCV from human liver chimeric mice[30].…”
Section: Vaccines To Prevent Primary Hcv Infectionmentioning
confidence: 99%